The Cat-and-Mouse Game in Sports: A Review of Research on Doping Violations and Sanctions - Zhang, Daiqian (Journal of Social Science and Humanities, 2024)
The phenomenon of enhancing athletic performance through the consumption of various substances has a long history, and the issue of doping has persisted as an unending battle that plagues the global sports community. In response, the World Anti-Doping Agency (WADA) was established in 1999, and after four revisions, the 2021 version of the World Anti-Doping Code (WADC) was finally enacted and implemented. This led to the formation of an anti-doping system led by WADA and centered on the WADC. The book Research on Doping Violations and Sanctions uncovers the inherent logical structure of the anti-doping system, Which is the first monograph on doping in China. Apart from discussing the anti-doping system at the substantive law level, the book also delves into diversified standards of proof and the protection of athletes' procedural rights at the procedural law level. To prevent the abuse of doping in sports, safeguard athletes' physical and mental health, and maintain fair competition, China has established a regulatory framework for anti-doping through a series of normative legal documents, including laws, administrative regulations, departmental rules, and judicial interpretations. Meanwhile, to ensure alignment with international anti-doping standards, countries need to continuously strengthen their domestic anti-doping legislation in accordance with the WADC. On November 20, 2024, the General Administration of Sport of China officially released a revised version of the Anti-Doping Rules, marking significant changes from the 2020 edition. This move fully demonstrates China's high regard for and continuous improvement in anti-doping efforts.